Neurosis - Continuum [ Architecture As Urban Therapy ] - Scriba, Christian (School of Architecture, Planning and Geomatics, 2017)
This dissertation is rooted within the personal struggle to understand the absurdity of spaces which exist within Woodstock, Cape Town. The project draws a psychological connection between the site and its absurdities, implying that spatial absurdity is the effect of problems of the personified "sitemind". By visualizing what are called "neurosis spaces" the expressions of site-mind anxieties, and arranging them into a speculative site, the project creates a space of analogy. A space for which architecture becomes a therapy. Architecture in application thereby embodies therapy, forming an intervention which itself enacts the speculative analogy. The proposal is therefore seated firmly between the real and the imagined. A victim Offender Rehabilitation center mediates the analogy physically creating an architecture that plays on spatial experience and programming to create a place of therapy, a machine of sublimation.